A Ductility-Centred Analytical Model for Axially Restrained Double-span Steel Beam Systems Subjected to Sudden Columns Loss. (May 2017) - Fu, Haoran; Zhang, Jinfan; Jiang, Jianqun; Wang, Zhenyu
Abstract: This paper presents a ductility-centred analytical model for robustness assessment of axially restrained double-span steel beam systems further to sudden columns loss. The main benefit of the model is its ability of linking the response of semi-rigid beam-to-column joints to the load carrying capacity of the system, and in addition, the model supports the use of codified methods for joint response. The analytical model is first validated through comparisons against detailed double-span FE models, where it is found that the load-joint rotation responses of the axially restrained systems can be accurately captured by the analytical model, especially at catenary stages. Comparisons are also made against the FE results excluding the axial restraints. The axial restraints are shown to play a crucial role in the development of catenary action. Following the verification study, the analytical predictions of the double-span beam systems with varying parameters were further presented and discussed, and an illustrative design example was finally given to clearly demonstrate the practical use of the analytical model for robustness assessment of building frames. The analytical model is design effective and hand-calculable, and thus it brings convenience to robustness assessment of structures in practice. The proposed method may be considered as a feasible alternative method to detailed nonlinear dynamic analysis.